The influence of neural networks on the practice of using academic essays in the educational process - Akushevich, Andrei A. (University Pedagogical Journal, 2025)
The experience of application of academic essays in modern educational institutions is considered. Positive and negative aspects of using neural networks in the practice of teaching pedagogical and philological disciplines are presented. Possible strategies of using artificial intelligence technologies in teaching the creation of texts (educational products), as well as examples of tasks aimed at developing studentsʼ competences in working with neural networks are offered.
Keywords: digitalisation of education; higher education; neural networks; teaching methods; academic writing; essay; competencies in working with neural networks